Composição química e propriedades tecnológicas dos grãos de cultivares de feijão (Phaseolus vulgaris L.) sob cultivo orgânico - Rufatto, Joceleide (2021)
Common bean a has a great nutritional, social and economic importance, as they are considered worldwide as one of the most important source in terms of production and consumption for human nutrition. The objective of this work was to carry out the characterization of the chemical composition and technological properties of the grains of thirteen bean cultivars under organic farming system. The experimento was conducted in a randomized block designThe thirteen common bean cultivars were sown under organic farming system in a no-tillage system. After the complete cycle of the beans, the grains were harvested and later the analyzes were carried out. The color was determined shortly after harvest. Subsequently, cooking time, total soluble sugars, proteins, total phenols, total tannins and mineral composition were analyzed. The data obtained were subjected to analysis of variance and when there was a significant difference by the F test, the means test to compare the cultivars was performed. There was no significant difference between cultivars for the total variables. The cultivar with the highest concentration of total soluble proteins present was BRSMG Madrepérola (18.81 g 100g-1). Regarding the concentration of total soluble sugars, the cultivars that stood out were BRS Campeiro (14.74 g 100g-1) and BRSMG Realce (14.10 g 100g-1). Among the cultivars analyzed, in relation to the total phenolic content, IACImperador (1.37 mg g-1 AT) presented the highest value. For total tannins, the cultivars that showed the lowest value were ANfc 9 (0.28 mg g-1 AT) and TAA Dama (0.39 mg g-1 AT). Regarding the color of the seed coat, for black grains the cultivars that stood out were BRS Intrépido (L* = 4.28) and IPR Uirapuru (L* = 4.74) (lower luminosities), and for carioca grains they were the ANfc9 (L* = 36.73), IPR Tangará (L* = 35.60), IPR Quero-Quero (L* = 34.67), IPR Andorinha (L* = 34.53) and BRSMG Madrepérola (L* 32.96) (higher luminosities). The cultivars that obtained the shortest cooking time were BRSMG Realce (23.5 min) and IPR Tangará (23.6 min). Reagrdin the mineral composition, there was no significant difference among cultivars for nitrogen, phosphorus, calcium and copper. For potassium, the cultivars that showed the highest content were BRS Intrépido (1.64 g 100g-1) and BRS Esplendor (1.63 g 100g-1), for iron, the cultivars that stood out were IAC Imperador (49.72 mg kg-1) and BRS Intrépido (47.90 mg kg-1), for zinc, IPR Tangará (40.23 mg kg-1) was the cultivar with the highest content of this nutrient. The results indicate that the common bean production in a organic farming system resulted in grains with satisfactory nutritional qualities